Lung, breast and bowel cancer treatment for Aboriginal people in New South Wales: a population‐based cohort study. Issue 6 (21st June 2021) - Fitzadam, Suzanne; Lin, Enmoore; Creighton, Nicola; Currow, David C.
Abstract: Background: Aboriginal Australians have higher cancer mortality than non‐Aboriginal Australians. Lower rates of cancer treatment among Aboriginal people can contribute to this. Aims: To investigate demographic, clinical and access factors associated with lung, breast and bowel cancer treatment for Aboriginal people compared with non‐Aboriginal people in New South Wales, Australia. Methods: Population‐based cohort study using linked routinely collected datasets, including all diagnoses of primary lung, breast or bowel cancer from January 2009 to June 2012. Treatment (surgery, radiotherapy or chemotherapy) within 6 months from diagnosis was measured. Access was measured using minimum distance to radiotherapy or hospital with a cancer‐specific multidisciplinary team, visit to a specialist and possession of private health insurance. Logistic regression modelling was employed. Results: There were 587 Aboriginal and 34 015 non‐Aboriginal people diagnosed with cancer. For lung cancer, significantly fewer Aboriginal than non‐Aboriginal people received surgery (odds ratio 0.46, 95% confidence interval 0.29–0.73, P < 0.001) or any treatment (surgery, chemotherapy or radiotherapy; odds ratio 0.64, 95% confidence interval 0.47–0.88, P = 0.006) after adjusting for sex, age, disease extent and comorbidities. They were less likely to have an attendance with a surgeon (27.0%, 62/230 vs 33.3%, 2865/8597, P = 0.04) compared with non‐Aboriginal people. There were no significant differences in cancer treatment for Aboriginal people compared with non‐Aboriginal people for breast or bowel cancers after adjusting for patient sex, age, disease extent and comorbidities. Conclusion: Aboriginal people were significantly less likely to receive surgery for lung cancer than non‐Aboriginal people and had fewer attendances with a surgeon, suggesting a need to strengthen referral pathways.